Optimizing achalasia diagnosis in the era of high‐resolution manometry: A Pakistani perspective - Sameen Abbas; Tayyab S Akhtar; Sampath Chinnam; Saima Mushtaq; Nafees Ahmad; Yu Fang; Amjad Khan (JGH Open)
Abstract Background High‐resolution manometry (HRM) is a gold standard for diagnosing achalasia and identification of its subtypes, but data regarding its correlation with clinical, endoscopic, and radiological features in low‐resource settings like Pakistan are limited. This study aims to identify and compare manometric parameters with other diagnostic parameters among achalasia subtypes in Pakistani population. Methodology A retrospective analysis of clinical, endoscopic, and radiological features of 381 patients who underwent HRM at Center for Liver and Digestive Diseases, Holy Family Hospital, Rawalpindi, Pakistan, from December 2015 to February 2024 was performed. Based on the HRM criterion, 213 patients were identified and categorized into subtypes: 132 cases for type I and 64 and 17 for type II and III, respectively. Results Patient demographics were similar across subtypes except for sex (male‐dominant in types I and II, female‐dominant in type III). Symptom duration was longest in type III (8 years vs. 4.1 years). Almost all patients had dysphagia; 83% reported regurgitation/weight loss, 71% chest pain, and 64% vomiting. The endoscopy results were normal in 40% of patients, and barium swallow was inconclusive in just 13% of achalasia patients. Type III exhibited the highest EGJ relaxation pressure and lowest LES pressure. Notably, all subtypes displayed elevated IRP, with type I showing highest value. Conclusion This study identified type I achalasia as the most prevalent subtype. While barium swallow and endoscopy showed limited diagnostic accuracy, HRM confirmed subtypes in all patients. Despite challenges with GERD‐like symptoms and inconclusive findings, further research is warranted to investigate specific clinical features of each subtype, potentially attributing to personalized treatment strategies.